Maturity Effect on Bid-Ask Spreads of OTC Currency Options - CHONG, Beng Soon (Institutional Knowledge at Singapore Management University, 2003)
The paper ascertains the relation between bid-ask spreads and the contract maturity of OTC currency options. Contrary to previous findings in the futures market, spreads of currency options are found to be negatively related to the contract's term-to-maturity. The negative relation persists even after controlling for the effects of price risks, competition, and trading activity. The pronounced differences in the term-to-maturity results are attributable to the market risk effect and differences in the market structure of options and futures markets.